Interpretation of the Inheritance Verses in Surah an-Nisa in the Toba Batak Tradition - Elsa Ade Putri Rambe; Agus Imam Kharomen (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Inheritance remains one of the most contested legal domains in Indonesia’s pluralistic society, where Islamic law and customary (adat) law frequently intersect and, at times, conflict. This tension is particularly pronounced within the Toba Batak community, which upholds a patrilineal inheritance system that prioritizes male heirs and often excludes women. This study aims to examine the concept of justice in Islamic inheritance law through a thematic exegesis (tafsīr mawdū‘ī) of Surah An-Nisā’ verses 7, 11, and 12, and to assess its relevance to the Batak Toba customary inheritance system. Employing a qualitative descriptive-analytical method and drawing primarily on Tafsīr al-Qurṭubī, the study finds that the Qur’an establishes a framework of proportional justice in which both men and women are granted inheritance rights based on social and financial responsibilities. The main finding of this study is that the exclusion of women in the Batak Toba inheritance system is not only inconsistent with Qur’anic principles but can be critically reconstructed through a justice-oriented interpretive approach. The findings reveal a significant gap between Qur’anic principles and the exclusionary nature of customary practices. This study argues that Islamic inheritance law offers not only a normative legal framework but also a transformative ethical foundation for reconstructing customary inheritance systems toward greater inclusivity and gender equity in contemporary society. Future research is recommended to incorporate empirical field studies to examine community responses and the practical challenges of implementing more equitable inheritance models.